Effect of lanthanum cerium methionine on the properties of natural rubber. Issue 2 (May 2022) - Li, Shuai; Liu, Zhaogang; Hao, Wei; Zhang, Wentao; Hu, Yanhong; Wu, Jinxiu
Lanthanum cerium methionine was synthesized using the metathesis method and its molecular formula was confirmed as La0.35 Ce0.65 Cl3 (C5 H10 NO2 S)3 ·2H2 O via Inductively Coupled Plasma Optical Emission Spectrometer, FTIR, and thermogravimetry-differential scanning calorimetry characterization methods. Lanthanum cerium methionine can significantly reduce the activation energy of the vulcanization reaction. The vulcanization kinetics model is used to fit the vulcanization curve of the rubber, and the obtained vulcanization activation energy of lanthanum cerium methionine for rubber is E1 = 76.89 KJ/mol, E2 = 102.36 KJ/mol and E3 = 126.00 KJ/mol. The above value is lower than pristine rubber. The Kissinger method and Flynn–Wall–Ozawa method were used to analyze the activation energy of thermal-oxidative degradation of vulcanized rubber. It was found that the rubber added with lanthanum cerium methionine exhibited higher thermal-oxidative degradation activation energy compared to that of pristine rubber; in addition, it was more difficult to age under the same environment. These results indicated that lanthanum cerium methionine can be not only used as a vulcanization accelerator, but also plays a role in resisting thermal and oxygen aging.